Detecting and Reporting Deceptive Prescription Drug Promotion: Differences Across Consumer and Physician Audiences and by Number and Type of Deceptive Claims and Tactics. Issue 13 (10th November 2022) - Betts, Kevin R.; O'Donoghue, Amie C.; Johnson, Mihaela; Boudewyns, Vanessa; Paquin, Ryan S.
ABSTRACT: The U.S. Food and Drug Administration's (FDA) Bad Ad program provides an avenue for healthcare providers to report false or misleading prescription drug promotion. Yet, whether healthcare providers can detect such promotion, and whether they believe it should be reported to FDA, remain open questions. Consumer audiences may also be capable of detecting such promotion and believe it should be reported, but even less is known about capability and belief in this population. Across two experiments using mock pharmaceutical websites, this research investigated capability to detect and inclination to report deceptive prescription drug promotion among a sample of primary care physicians and consumers. Study 1 varied the number of deceptive claims and tactics on a website for a chronic pain medication, operationalized as none, two, or five. Study 2 varied the type of deceptive content on a website for a weight loss medication, operationalized as none, implicit, or explicit. Findings reveal that, in line with expectations from FDA's Bad Ad program, physicians can detect deceptive promotion and tend to believe it should be reported. Consumers are also capable of detecting deceptive promotion and tend to believe it should be reported, but their capabilities and beliefs regarding reporting are generally lower.